Association between Dietary Antioxidant Capacity in Midlife and Depressive Symptoms in Late Life: The Singapore Chinese Health Study - Huiqi Li; Li-Ting Sheng; Bee Choo Tai; An Pan; Woon-Puay Koh (MDPI AG, 2024)
Preclinical and limited epidemiological studies suggest that oxidative stress may be implicated in geriatric depression. Our study investigated the association between midlife dietary total antioxidant capacity (TAC) and depressive symptoms in late life among 13,712 participants in a population-based cohort of Chinese in Singapore. At baseline (1993-1998), intake of antioxidants from diet and supplements at a mean age of 52.4 years was estimated using a validated food frequency questionnaire to derive two dietary TAC indices from vitamins C and E, carotenoids and flavonoids: the Comprehensive Dietary Antioxidant Index (CDAI) and Vitamin C Equivalent Antioxidant Capacity (VCEAC). At follow-up 3 (2014-2016), when participants were at a mean age of 72.5 years, depressive symptoms were assessed using the Geriatric Depression Scale, and depression, defined as having ≥5 symptoms, was presented in 3173 (23.1%) participants. Both CDAI and VCEAC indices were inversely associated with odds of depressive symptoms in a stepwise manner: the OR (95% CI) comparing the extreme quartiles was 0.73 (0.64-0.83; Ptrend < 0.01) for the CDAI and 0.77 (0.68-0.87; Ptrend < 0.01) for the VCEAC. Specifically, higher intakes of vitamin C, carotenoids, and flavonoids were associated with a lower likelihood of depressive symptoms. Our findings support the recommendation of an antioxidant-rich diet for the prevention of depression.